2021
DOI: 10.1128/msystems.01186-20
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Sulfur Oxidation Underlies Adaptation of a Chemosynthetic Symbiont to Oxic-Anoxic Interfaces

Abstract: Chemoautotrophic endosymbionts are famous for exploiting sulfur oxidization to feed marine organisms with fixed carbon. However, the physiology of thiotrophic bacteria thriving on the surface of animals (ectosymbionts) is less understood.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 170 publications
0
26
0
Order By: Relevance
“…To understand the molecular mechanisms underlying L. oneistus response to oxygen, we subjected it to various oxygen concentrations. Namely, nematode batches were incubated under either normoxic (100% air saturation; O), hypoxic (30% air saturation; H) or anoxic (0% air saturation; A) conditions for 24 h. Additionally, given that L. oneistus thrives in reduced sand containing up to 25 µM sulfide 16 , 17 , we also incubated it in anoxic seawater supplemented with < 25 µM sulfide (anoxic sulfidic condition; AS; see 16 for the sulfide concentration experienced by L. oneistus during each incubation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the molecular mechanisms underlying L. oneistus response to oxygen, we subjected it to various oxygen concentrations. Namely, nematode batches were incubated under either normoxic (100% air saturation; O), hypoxic (30% air saturation; H) or anoxic (0% air saturation; A) conditions for 24 h. Additionally, given that L. oneistus thrives in reduced sand containing up to 25 µM sulfide 16 , 17 , we also incubated it in anoxic seawater supplemented with < 25 µM sulfide (anoxic sulfidic condition; AS; see 16 for the sulfide concentration experienced by L. oneistus during each incubation).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas transcriptional differences of the symbiont Candidatus Thiosymbion oneisti incubated under normoxic (O) and hypoxic (H) conditions were negligible 16 , the expression profiles of nematode batches incubated under O conditions varied so much that they did not cluster (Fig. S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…If, based on transcriptomics, Ca. T. oneisti might import phospholipids, ammonia, and organic compounds from its host and sulfide, oxygen, urea, and CO 2 from the environment ( Paredes et al., 2021 ), we still do not know which molecules Thiosymbion cells exchange among themselves. Therefore, the physiological needs that would drive the evolution of a cube-like cell await discovery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed an upregulation of transporter genes, indicating heterotrophy under oxic conditions in Cand. Thiosymbion oneisti, the thiotrophic ectosymbiont of the marine nematode Laxus oneistus [45]. Although genes that support this function are present in the metagenome assembled genome of Thiobius (Espada-Hinojosa pers.…”
Section: Plos Onementioning
confidence: 99%